1998
DOI: 10.1007/s004210050425
|View full text |Cite
|
Sign up to set email alerts
|

Energy and substrate metabolism during a 42-day bed-rest in a head-down tilt position in humans

Abstract: Microgravity-induced changes in body composition (decrease in muscle mass and increase in fat mass) and energy metabolism were studied in seven healthy male subjects during a 42-day bed-rest in a head-down tilt (HDT) position. Resting energy expenditure (REE), fat and glucose oxidation were estimated by indirect calorimetry on days 0, +8 and +40 of the HDT period. Assessments were performed both in post-absorptive conditions and following two identical test meals given at 3-h intervals. Body composition (dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…Demaria-Pesce et al (1992) showed a reduction in spontaneous intake in three subjects during 28d bed-rest in an HDT position. We have observed similar findings during 42 d bed-rest in the study mentioned previously (Ritz et al 1998). While this latter study was not specifically designed to examine in detail appetite sensations and feeding behaviour, a number of interesting patterns emerged.…”
Section: Energy and Macronutrient Intakesupporting
confidence: 83%
“…Demaria-Pesce et al (1992) showed a reduction in spontaneous intake in three subjects during 28d bed-rest in an HDT position. We have observed similar findings during 42 d bed-rest in the study mentioned previously (Ritz et al 1998). While this latter study was not specifically designed to examine in detail appetite sensations and feeding behaviour, a number of interesting patterns emerged.…”
Section: Energy and Macronutrient Intakesupporting
confidence: 83%
“…10 Usual physical activity modulates resting fat oxidation, as it is higher in very active young and elderly persons than in sedentary ones. 7,9,10 Furthermore, resting fat oxidation is reduced by bed-rest 12 and increased by endurance training in young 13 ± 15 and elderly subjects. 16 ± 18 Since their usual physical activity is reduced, 19 elderly persons are expected to show a lower fat oxidation than young subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed sleeping fat oxidation represents about 24% of daily fat oxidation. 18 The remaining 76% can be in¯uenced by physical activity (since for low-intensity exercise fat is the main fuel 37 ) and by meals (since carbohydrates decrease fat oxidation, 12,38 ). Sial et al 10 have shown that, when compared to young subjects, elderly men (or women) rely more on fat than on glucose for energy production during exercise.…”
Section: Decreased Fat Oxidation With Aging E Levadoux Et Almentioning
confidence: 99%
“…After 7 days of head-down bed rest, fasting lipid oxidation was reduced by ~80% in both men and women (14). Similarly, in a study by Ritz et al (127), fat oxidation during fasting was significantly lower and carbohydrate oxidation higher following long-term simulated microgravity (42 days). In addition, both fasting and insulin-stimulated levels of lipogenesis were significantly increased in women following 7 days of bed rest (14).…”
Section: Effect Of Physical Inactivity On Substrate Metabolismmentioning
confidence: 83%